A New Link in a Chain of Genres? - Swales, John M.; Jakobsen, Henriette; Kejser, Christina; Koch, Lena; Lynch, Joan; Mølbæk, Lone (HERMES - Journal of Language and Communication in Business, 2000)
Institutional genres often form dynamic systems or chains. In this paper we report on a possible expansion of the genre system that undergirds the appointment process of assistant professors in the U.S. This expansion consists of a “response letter” to a letter of recommendation. We first analyse a small corpus of these response letters by looking at the openings and closings and the bodies of the letters. The larger aim of this analysis is to explore the possible rationales that might underlie the composition, stylistic character and content of these texts.